Comparative Analysis of the Influence of Financial Performance on the Capital Structure of Food and Beverage and Transportation Services Companies Listed on the IDX - Raulian Franciskus Pasaribu; sumilir sumilir; Yudi Nur Supriadi (Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study examines the factors that affect the capital structure of food and beverage sub-sector companies and transportation services sub-sectors listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The study also examines the comparison of the capital structure of food and beverage companies with transportation services during the 2020-2022 period. Sample determination technique using the purposive sampling method, the selection of samples from 25 companies in the food and beverage sub-sector resulted in 15 companies being accepted. Then from 36 companies in the Transportation Services sub-sector, 15 companies were accepted. Data analysis was carried out using Microsoft excel, Hypothesis testing using multiple linear regression analysis and differential test using Indpendent sample t-test with SPSS 23 program with a significance level of 5%. The test results were obtained that the profitability variable had a negative effect on the capital structure of the food and beverage company and transportation services. Next, the sales growth variable has no effect on the capital structure of food and beverage companies and transportation services. For food and beverage companies, the size of the company has no influence on the capital structure. However, unlike transportation service companies, the company size variable has a positive influence on the capital structure. The results of the study also show that there is a significant difference in capital structure between food and beverage companies and transportation services. Keywords: Profitability, sales growth, company size, capital structure, and independent sample t-test.